Effects of process parameters on selected properties of liquid compression-molded vinyl ester sheets - Abd. Rahman, Mohamed; Salit, Mohd Sapuan; Mridha, Shahjahan; Abdan, Khalina (2009)
Vinyl esters combine the best of polyesters and epoxies in terms of properties and processing. Without complicating presence of reinforcing fibers, this study investigated the effects of catalyst amount, preheating time, molding temperature and pressure on flexural properties and water absorption of cast vinyl ester (VE) using a factorial experiment. All four factors did not affect the flexural properties of molded VE significantly. Using high molding pressure however caused higher water absorption. Molded VE-unsaturated polyester (UP) blend was a significantly different material which was 1.49 times stronger, 2.38 times more flexible but 0.69 less stiff than neat VE and with significantly worse water absorption property. The results obtained warrant further investigation in process optimization of VE molding and use of VE-UP blend as matrix for natural fiber-reinforced composites.